Medically Assisted Procreation and the constitutional principles of equality and non-discrimination - BRAGA, Fátima (Revista Jurídica Portucalense, 2023)
The LPMA, dated 2006, was subject to legislative changes that adjusted it to the needs of an evolving society, reflecting other legislative options that necessarily influence it. These alterations reside in the abandonment of the subsidiary character conferred on the use of PMA, for an alternative possibility, available to any woman and independent of a diagnosis of infertility. The traditional principle of biological truth in establishing filiation suffered compressions in cases of heterologous insemination, establishment of double maternity and surrogacy. By allowing single women to use the PMA, the concern of not promoting single-parent families is abandoned. Considering the relevance of the constitutional principles of equality and non-discrimination, associated with the changes undergone by the LPMA, we did not find any valid basis for the removal of men, alone or male couples, as beneficiaries of the PMA. We conclude for the unconstitutionality of n.º 1 of art. 6 of the LPMA insofar as it denies men, alone or male couples, the possibility of resorting to the PMA as a means of ensuring procreation, which should be available to all people, respecting and implementing the principles of equality and non-discrimination.